THERAPEUTIC POTENTIAL OF ALOE VERA EXTRACT ON HAEMATOLOGY, HEPATOXICITY, AND NEPHROTOXICITY INDUCED BY COPPER IN LABEO ROHITA - Mariam Khalid, Nimra Naseer, Dr. Amara Akhtar, Muhammad Faraz Haider, Awais Zia, Muhammad Ahmed Saqib (Chelonian Research Foundation, 2024)
An experiment was conducted to find the therapeutic potential of Aloe vera extract on haematology, hepatotoxicity and nephrotoxicity induced by copper in Labeo rohita. Four treatments were made. T0 served as the controlled treatment. Juveniles in the T1 were exposed to 15 mg/L CuCl2 while those in T2 were exposed to 20 mg/L CuCl2. Juveniles in the T3 were exposed to 25 mg/L CuCl2 for 21 days. After this period all groups of fish were supplemented with 20g/kg Aloe vera extract for one week. At the end of the trial, both haematological parameters and the histopathology of the liver and kidney were analyzed. The results showed a substantial decrease in RBCs, haemoglobin (Hb) and haematocrit (HCT) values across all metal-treated groups T1, T2, and T3 as compared to the control group. The control group T0 (2.05±0.05) had the greatest RBC count after receiving 0 mg/L of copper chloride. The lowest RBC count was seen in group T3 (0.63±0.175). The control group T0 had the greatest haemoglobin level (2.99±0.027) while the lowest amount was found in group T3 (0.70±0.53). T3 group had the greatest white blood cells count (18.6±0.36) while the T0 control group had the lowest (11.64±0.050). The control group T0 had the highest platelet count (23.5±0.9) whereas group T3 had the lowest (9.71±0.7). The haematological parameters examined included haematocrit (Hct), haemoglobin (Hb), platelets, red blood cells (RBCs), white blood cells (WBCs), mean corpuscular volume (MCV). Copper chloride-induced hepatotoxicity appeared as hepatocyte inflammation, necrosis, clumped chromatin and cytoplasmic vacuolization. For histopathological analysis kidney were stained and examined under a compound microscope to identify any structural changes or damage. Data collected from these analyses were statistically analyzed using one-way ANOVA to determine the significance of differences between the control and treated groups.